Peran Green Accounting dalam Mewujudkan Prinsip Pembangunan Berkelanjutan - Mubarokah, Annisa Kharirotul; Setyaningsih, Nina Dwi (Universitas Gorontalo, 2024)
Environmental accounting is an important part of improving a company's environmental performance. Green accounting is a concept developed in Europe in 1970. This concept is used to identify, prioritize, and incorporate environmental costs in business decision making. By using green accounting, companies can reduce environmental problems and increase the effectiveness of environmental management. Despite this, the use of green accounting is still limited in developing countries. This research uses a qualitative descriptive data collection method which includes observation, interviews, documentation and triangulation. The findings show that Bakpia Maharani MSMEs face challenges related to waste management and financial reporting, because they do not allocate costs for prevention and detection, but instead focus on waste processing. This research aims to determine the implementation of green accounting in Bakpia Maharani MSMEs and identify related challenges.